Academician B.V. Petrovsky: cultural heritage, historical memory - K. V. Kotenko; M. Sh. Khubutiya; S. A. Kabanova; Yu. S. Goldfarb (Трансплантология (Москва))
In 2023, the medical community of Russia is celebrating two closely related significant historical events. They are the 115th anniversary from the birth of B.V. Petrovsky, an outstanding personality in Russian medicine, Academician of the Russian Academy of Sciences, and the 60th anniversary from the foundation of Petrovsky National Research Center of Surgery.The article presents little-known materials related to the cultural heritage of B.V. Petrovsky and keeping the historical memory of him. The paper esteems B.V. Petrovsky's activity as the founder of the Russian Scientific Center for Surgery and a reformer of higher medical education.